Pyroptosis-Related Signature and Tumor Microenvironment Infiltration Characterization in Head and Neck Squamous Cell Carcinoma - Wu, Zeng-Hong; Wu, Bian; Li, Cheng; Zhang, You-Jing; Zhou, Tao (Frontiers in Cell and Developmental Biology, 2022)
Background: Head and neck squamous cell carcinoma (HNSCC) ranking as the sixth most widespread and deadly cancer. Until now, very few studies have systematically evaluated the role of pyroptosis-related genes (PRGs) and lncRNAs in HNSCC patients. Methods: We integrated the genomic data to comprehensively assess the role of pyroptosis with the tumor microenvironment (TME) cell-infiltrating characteristics in HNSCC. Besides, we also constructed a set of scoring system to calculated the pyroptosis dysfunction in each patient. Results: The analysis of CNV alteration frequency displayed that CNV changes were common in 33 PRGs, and the frequency of copy number gain and loss was similar. CASP8 demonstrated the highest mutation frequency. Considering the individual heterogeneity, a scoring system to quantify the pyroptosis pattern in each patient was constructed based on these phenotypic related genes, which we named as PyroptosisScore. The results indicated that low PyroptosisScore group experienced increased extensive TMB than the high group, with the most significant mutated gene was TP53 and TTN. Finally, we tried to found some useful pyroptosis-related lncRNA and 14 differently expressed lncRNAs were selected as independent prognosis factors of HNSCC patients based on the multivariate Cox analysis. Conclusion: This work suggests the pyroptosis features and the potential mechanisms on tumor microenvironment. The exploration may assist in identifying novel biomarkers and help patients to predict prognosis, clinical diagnosis, and management.